2022
DOI: 10.3390/nano12030328
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Ruthenium Catalyst Modification for the Conversion of Furfural to 1,2-Pentanediol

Abstract: Exploiting biomass to synthesise compounds that may replace fossil-based ones is of high interest in order to reduce dependence on non-renewable resources. 1,2-pentanediol and 1,5-pentanediol can be produced from furfural, furfuryl alcohol or tetrahydrofurfuryl alcohol following a metal catalysed hydrogenation/C-O cleavage procedure. Colloidal ruthenium nanoparticles stabilized with polyvinylpyrrolidone in situ modified with different organic compounds are able to produce 1,2-pentanediol directly from furfural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Bruna et al utilized amine in situ modified Ru/PVP catalyst for the first time to generate 1,2-PeD directly from FF, with 36 % selectivity of 1,2-PeD at 125 °C under 2 MPa H 2 . [108] Pisal et al synthesized a polyphasic mixed-valent octahedral molecular sieve impregnated with rhodium (Rh/OMS-2) catalyst by hydrothermal method for FF hydrogenolysis to 1,2-PeD. [23] It was found that OMS-2 with both base and metallic sites is the key to obtain high selectivity of 1, 2-Ped.…”
Section: Production Of 12-pentanediol(12-ped) and 15-pentanediol(15-ped)mentioning
confidence: 99%
See 1 more Smart Citation
“…Bruna et al utilized amine in situ modified Ru/PVP catalyst for the first time to generate 1,2-PeD directly from FF, with 36 % selectivity of 1,2-PeD at 125 °C under 2 MPa H 2 . [108] Pisal et al synthesized a polyphasic mixed-valent octahedral molecular sieve impregnated with rhodium (Rh/OMS-2) catalyst by hydrothermal method for FF hydrogenolysis to 1,2-PeD. [23] It was found that OMS-2 with both base and metallic sites is the key to obtain high selectivity of 1, 2-Ped.…”
Section: Production Of 12-pentanediol(12-ped) and 15-pentanediol(15-ped)mentioning
confidence: 99%
“…Among them, 1,2‐PeD is a key raw material in the synthesis of the fungicide propiconazole [23] . 1,5‐PeD is used as a solvent for cutting oils, special detergents, latex paints, and as an intermediate for the manufacture of chemicals such as plasticizers, brake oils, alkyd resins, and polyurethane resins [24,108] . They can be obtained by ring‐opening hydrolysis of THFA or by direct ring‐opening hydrolysis of FA.…”
Section: Conversion Of Ff To Renewable Value‐added Chemicalsmentioning
confidence: 99%
“…In addition to the adsorption and hydrogenation of FF to FA on metallic catalysts, acid-base sites affect the bond cleavage position and the selectivity of the reaction (Figure 4). Bruna et al [39] prepared colloidal Ru particles with polyvinylpyrrolidone modified with different organic compounds to produce 1,2-PeD and 1,5-PeD from FF, FA, and THFA. The amine-modified Ru/PVP catalyst could be efficiently used for the production of n-PeD directly from FF.…”
Section: Pentanediolmentioning
confidence: 99%
“…Among the investigated catalysts, Pt-and Ru-based catalysts were usually favorable for the production of 1,2pentanediol (1,2-PeD), while Rh-and Ir-based catalysts were more conducive to 1,5-PeD generation. 7 However, noble metal catalysts usually face problems such as high cost, poor stability, and long reaction duration. A multistep method with different catalysts (Ni, γ-Al 2 O 3 , and Ru) at sequential steps has also been reported to produce 1,5-PeD.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have investigated the production of diols from THFA over different catalysts, as briefly summarized in Table . Among the investigated catalysts, Pt- and Ru-based catalysts were usually favorable for the production of 1,2-pentanediol (1,2-PeD), while Rh- and Ir-based catalysts were more conducive to 1,5-PeD generation . However, noble metal catalysts usually face problems such as high cost, poor stability, and long reaction duration.…”
Section: Introductionmentioning
confidence: 99%